(3GdeSGhGI Hjf GdNUhe ai GdOYhi GdLfGFjI (B/ s - (3GMSGf YHOGdYRjR GdUGdM GdSdGeGJs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3jYO eHOC GdeSGhGI ef Sff GdaWQI GdchfjI ddHTQ(B: (3h GdQGSNI ai CYeGb GdfaS GdHTQjI efP HOA GdNdjbI(B: (3Pdc Cf gPG GdeHOC ef CfHd GdMbhb GdEfSGfjI GdJi JUHh cGaI GdeLJeYGJ Edi SjGOJg h Sehg(B: (3h bO MQUJ GdTQGFY GdSeGhjI h GdOSGJjQ GdOhdjI OheG Ydi JCcjO EQSGA gPG GdeHOC HGYJHGQg Gdgjcd GdQFjSi ddcjGf GdEfSGfi PGJg(B. (3h JYfi GdeSGhGI ai UhQJgG GdeLQOI Ch GdeKGdjI YOe GdJejjR Hjf GdCaQGO HSHH GdCUd Ch GddZI Ch GdLfS Ch GdYbjOI Ch GdKQhI(B: (3h dcf gPG Gdeaghe GdeKGdi jUWOe HbhI GdhGbY GdYedi(B: (3h jCJi Pdc ef GNJdGa GdCaQGO ef MjK GdbOQGJ h GdehGgH h GdGSJYOGO GdaWQi h GdSeGJ GdTNUjI(B. (3h dYd GdeJHGOQ ddCPgGf ddhgdI GdChdi JWHjbG deHOC GdeSGhGI(B: (3gh VQhQI Cf JTed GdYOGdI LejY GdCaQGO(B: (3h Cf jchfhG LejkYG eJSGhjjf ai GdMbhb h GdhGLHGJ(B: (3h ef GdfGMjI GdLfGFjI GdYbGHjI Ch GdELQGFjI Cf jchfhG LejkYG Ydi bOe GdeSGhGI(B. (3h dcf ef Gdeaghe GdfXQi GdHMJ dG jecf GdCNP Hg Ydi Yeheg(B: (3h Pdc dhLhO GYJHGQGJ YOjOI efgG eG jaQVg GdhGbY GdYedi(B: (3h efgG eG JaQVg VQhQGJ GdMjGI ai eLJeY JJHGjf ajg GdeUGdM h JJYGQV ajg CfeGW GdSdhc GdEfSGfi(B: (3MjK Cf GdGYJHGQ GdChd dcd aQO ef GdCaQGO gh PGJg h eUGdMg(B: (3aVkdG Yf GdJYGQV ai cKjQ ef GdCMjGf Hjf eUdMI GdaQO h eUdMI GdLeGYI(B: (3h ELQGA GdehGRfI dJaVjd CjgeG Ydi GdCNQis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2021s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B411-460s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdNUhes; (3GdOYhi GdLfGFjIs; (3GdeSGhGIs; (3GdeSGhGI aj GdGSdGe s; (3GdJfGSH Hjf GdLQjeI hGdYbhHIs; (3GdQbGHI Ydj OSJhQjI GdbhGfjfs; (3GdbVGA GdWHjYjs; (3eXGgQ GdGNdGd HeHOC GdeSGhGIs; (3GdMUGfI GdHQdeGfjIs; (3JSHjH GdGMcGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs